The adoption of the Internet of things by young consumers: An empirical investigation - Radosław Mącik (Economic and Environmental Studies (E&ES), 2017)
On the background of theoretical considerations and literature review, this article presents the results of the preliminary study of young consumers about their adoption of the Internet of Things (IoT) - treated as the emerging technology, creating a new quality of information technology usage, despite perceived costs and privacy concerns. The data for the analysis came from purpose sample of 223 young consumers from Eastern Poland via CAWI questionnaire. The primary goal of the research was to explore the adoption of IoT by young consumers in Poland regarding the level of adoption and factors explaining this phenomenon. The main analysis used univariate analysis of variance (UNIANOVA) and covariance-based structural equation modelling (CB-SEM). The current level of adoption of IoT by young consumers looks rather high (80% of respondents used at least one IoT-enabled device), although 78% of owners of IoT devices were not aware of Internet of Things concept. Study participants rather declared the usage of connected things recognised by connecting technology (Wi-Fi, Bluetooth), than the conscious usage of IoT. Among factors influencing IoT adoption the Performance expectancy and Habit constructs, as well as Personal innovativeness in the domain of information technology (PIIT), had an impact on Behavioural intention to use IoT. For some groups of devices, the gender impact was significant. Declared income, including lack of funds as the reason of not to use IoT, was not relevant as an explanatory variable.
Keywords: O33; D12; 330; Internet of Things; IoT; consumers; information technology adoption; preliminary model